Ethical and Inclusive Adoption of Artificial Intelligence in Education: A Conceptual Review and Institutional Framework - Rijois Saragih (International Journal of Information System and Innovative Technology, 2026)
The adoption of Artificial Intelligence (AI) in education has created significant opportunities for personalized learning, scalable educational services, and improved administrative efficiency. However, the increasing integration of AI technologies has also introduced ethical and inclusivity challenges, including data privacy concerns, algorithmic bias, unequal access to digital resources, and limited institutional readiness. This study presents a conceptual review of ethical and inclusive considerations in AI adoption within educational environments. Relevant literature published between 2019 and 2024 was analyzed through thematic synthesis to identify key dimensions influencing responsible AI implementation. The findings reveal four critical dimensions: ethical governance, inclusivity and accessibility, institutional readiness, and human–AI collaboration. Based on these dimensions, an institutional framework is proposed to guide educational institutions in implementing AI technologies responsibly while promoting equitable and inclusive learning environments. The framework emphasizes organizational governance, policy alignment, capacity building, and human-centered practices rather than technical system optimization. The proposed framework may serve as a practical reference for educational leaders, policymakers, and practitioners seeking sustainable and responsible AI adoption in education.